1990
DOI: 10.1093/geronj/45.5.p181
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric and Physical Morbidity Effects of Caregiving

Abstract: Existing empirical literature on the prolonged or cumulative consequences of exposure to the stresses of caregiving is reviewed. Specific goals are to identify psychiatric and physical morbidity effects, report the magnitude of those effects, evaluate research and analytic methods used to assess morbidity, and make recommendations for future research. Overall, the literature indicates increases in self-report psychiatric symptomatology and increases in psychiatric illness among most caregivers when compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
354
1
8

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 580 publications
(377 citation statements)
references
References 0 publications
14
354
1
8
Order By: Relevance
“…Specifically, while mean levels of depressive and anxiety symptoms were lower than the typical levels observed in dementia caregivers (e.g. CES-D scores from 14 to 16, Schulz et al, 1990;Baumgarten et al, 1992;Schulz et al, 1995;Wijeratne, 1997), they were only slightly higher than levels seen in healthy non-caregiving elderly cohorts (e.g. CES-D scores from 7.4 to 9.4, Blazer et al, 1991).…”
Section: Discussionmentioning
confidence: 61%
“…Specifically, while mean levels of depressive and anxiety symptoms were lower than the typical levels observed in dementia caregivers (e.g. CES-D scores from 14 to 16, Schulz et al, 1990;Baumgarten et al, 1992;Schulz et al, 1995;Wijeratne, 1997), they were only slightly higher than levels seen in healthy non-caregiving elderly cohorts (e.g. CES-D scores from 7.4 to 9.4, Blazer et al, 1991).…”
Section: Discussionmentioning
confidence: 61%
“…3 A significant amount of family suffering also occurs because of mental disorders. Schulz, Visintainer, and Williamson (1990) reviewed evidence showing that the cumulative effects of caring for someone with mental illness increase the caregiver's chances for a psychological disorder, as well as physical illness. Martens and Addington (2001) found that family members are stressed substantially by having to care for a relative with schizophrenia.…”
Section: Mental Disorders Are a Major Cause Of Low Well-beingmentioning
confidence: 99%
“…However, a large body of literature suggests that the chronic stress associated with providing care to a loved one with AD can have a deleterious impact on physical and mental health. Indeed, caregiving has been associated with increased risk for illnesses and diseases(7) such as coronary heart disease(8, 9). …”
Section: Objectivementioning
confidence: 99%
“…Schubert and colleagues(11)found that over a 6-month period, 24% of dementia caregivers had an emergency department visit or hospitalization, with depressed caregivers being at greatest risk. Perhaps the increased rate of service utilization among caregivers is due to increased mental and physical health morbidity, including increased risk of mortality compared to non-caregivers (12)and high rates of psychiatric problems including depression and anxiety (7, 13). For example, Dura and colleagues report that dementia caregivers are significantly more likely to have a depressive disorder compared to demographically matched non-caregivers (14).…”
Section: Objectivementioning
confidence: 99%